Application of hydroxyapatite granules in posterolateral intertransverse lumbar spinal fusion - Buyong, Zunariah; Zakaria@Mohamad, Zamzuri; Khalid, Kamarul Ariffin; Zulkifly, Ahmad Hafiz; Abdel Wahab, Emad Mohamad Nafie; Ab Rahman, Jamalludin; Abdul Rashid, Mohd Amran (2012)
In many clinical disciplines used of bone graft is unavoidable such as to replace bone loss due to trauma, to fill in bone defect after tumour excision, for reconstructive surgery or spinal fusion. Calcium phosphate based hydroxyapatite is widely used bone graft substitute due to its similarity with the mineral components of bone matrix. This study was conducted to evaluate bone formation effect of this biomaterial in posterolateral intertransverse lumbar fusion, a novel site for its application. Twelve adult New Zealand white rabbits underwent bilateral intertransverse lumbar spinal fusion at L5-L6 vertebrae. One site of the animals was implanted with hydroxyapatite granules (HA group) while the contralateral sides received autograft and served as the control (AUTO group). Bone formation was assessed at 6 and 16 weeks by undecalcified histology and scanning electron microscopy. New bone was formed on the surface of hydroxyapatite granules and continually formed even at 16 weeks. Close contact between new bone and hydroxyapatite granules was demonstrated by scanning electron microscopy.